I'm not playing: gamification, mental illness, and neoliberal subjectivity. - Russell, Francis (Journal for Cultural Research, 2018)
For many researchers, medical professionals, and politicians, the gamification of mental health treatment is a possibly innovative and efficient means to utilise the popularity of gaming in order to help combat the ever-growing global rates of mental illness. Despite this optimism, critics of gamification point to this trend as an extension of neoliberal governance, warning that gamification only encourages the further quantification and control of life under metrics of utility, productivity, and competitiveness. Accordingly, this article critically examines the politics of gamifying mental healthcare, and the broader question of the link between play and mental health. By engaging with the works of Donald W. Winnicott, and a host of contemporary critical and cultural theorists, this article attempts to open up a space for considering the value of play and games for sufferers of mental illness, that resist the strictures of the neoliberal governance of play.